DINAMIKA JURUSAN TAFSIR HADIS UIN IMAM BONJOL PADANG - Syafruddin, Syafruddin; Chalida, Sri; Idris, Mhd. (Universitas Islam Negeri Imam Bonjol Padang, 2020)
This study aims to determine the history of the establishment of the Department of Tafsir hadis at the Faculty of Ushuluddin and Religious Studies at IAIN Imam Bonjol Padang (now it has changed its status to UIN Imam Bonjol Padang). In addition, this research also wants to know the results of the tracer study of the Tafsir Hadis Department graduates. This research is a field research (field research) using a qualitative approach that is descriptive analytical. In addition, this study also uses the phenomenological approach developed by Husserl. This research was conducted for 3 months in Padang starting from June to August 2017. The results showed that the history of the establishment of the Tafsir Hadis Department at the Faculty of Ushuluddin IAIN Imam Bonjol Padang, began in 1989 with the transfer of the Tafsir Hadis Department which was previously in the Sharia Faculty to the Ushuluddin Faculty of IAIN Imam Bonjol Padang. The results of the tracer study of graduates show that the majority of alumni do not need a long time to get a job, approximately 1 - 6 months after completing their education. Besides, their work is relevant to the education they get.